LEADERSHIP STYLE, DISCIPLINE, MOTIVATION AND THE IMPLICATIONS ON TEACHERS'PERFORMANCE - Cicih Ratnasih (IJHCM (International Journal of Human Capital Management), 2017)
This study aims to determine the effect of leadership style, discipline, motivation and performance either partially or simultaneously in East Jakarta area.This study is using quantitative method. Total population in the human resource development as the study sample counted as many as 112 respondents. The sampling technique is using purposive sampling.The variables in this study areindependent variable, consist of leadership style, discipline, motivation and performance, and the dependent variable consist. Tests proved that motivation has a positive influence on the performance of teachers. Looking at the calculationsthat have been done the coefficient values obtained is 0.416 and t-count value is 5.984 with a significance level of 0.000 which less than 0.05, means that this hypothesis accepts Ha and reject Ho, Tests proved that the style of leadership have a positive impact on teacher performance. Judging from the calculations that have been done obtained coefficient value of 0.421 and t-count value of6.446 with a significance value of 0.000, smaller than 0.05. Thus, Ha is accepted and Ho is rejected., The tests proved that the discipline of work has a positive influence on the performance of teachers. Judging from the calculations that has been done obtained coefficient value of 0.151 and the t-count value of 2.055 with a significance level of 0,042 which smaller than 0.05, means that the hypothesis in this research reject Ho and accept Ha. The results showed that the leadership style, discipline, and motivation partially have significant effect on performance ofaudit quality in East Jakarta area.Leadership style, discipline, motivationsimultaneously have significant effect on performance with coefficient of determination 81.6%. Keywords: Leadership Style, Discipline, Motivation, Teacher Performance